1991
DOI: 10.1007/bf00010427
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of root colonisation of legumes by vesicular-arbuscular mycorrhizal (VAM) fungi through the inoculation of the legume seed with commercial yeast (Saccharomyces cerevisiae)

Abstract: Nodule number, dry weight of shoot and root biomass of legumes (Leucaena leucocephala, Glycine max, Cajanus cajan, Phaseolus mungo, Phaseolus aureus, Vigna unguiculata) were enhanced by inoculation with live yeast cells (Saccharomyces cerevisiae). Root infection (native VAM) and the formation of vesicles, arbuscules and spores were also increased with yeast inoculation. The increase in the parameters varied with legume and the type of yeast culture. Perceptable differences in the effectiveness of yeast culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…betaine) which are released by the yeasts during their growth. Singh et al [44] reported that yeasts or just their soluble exudates stimulated the percentage of soybean roots colonized by AMF and also the percentage of spore germination and hyphal growth [45]. This occurred particularly when the yeasts were inoculated as an aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…betaine) which are released by the yeasts during their growth. Singh et al [44] reported that yeasts or just their soluble exudates stimulated the percentage of soybean roots colonized by AMF and also the percentage of spore germination and hyphal growth [45]. This occurred particularly when the yeasts were inoculated as an aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…When G. geosporum and R. glutinis coexist in soil without the toxicant present, the fungus species shows a progressive increase in external mycelium development. Singh et al (1991) found that inoculation with yeast cells of Saccharomyces cerevisiae enhances symbiotic parameters such as spore number, formation of vesicles and arbuscules, and colonization. Another response is noted when G. geosporum lives with R. glutinis in soil with phenanthrene.…”
Section: Discussionmentioning
confidence: 98%
“…Stimulation of mycorrhiza formation by flavonoids and fungicides as well as by other microorganisms has been reported Singh et al, 1991;Siqueira et al, 1991;von Alten et al, 1993). Synergistic effects of rhizobia on mycorrhiza were thought to be nutritional and restricted to the stage of nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%